The impact of road traffic context on secondary task engagement while driving - Cuentas-Hernandez, Sandra; Li, Xiaomeng; King, Mark J.; Oviedo-Trespalacios, Oscar (Frontiers in Psychology, 2023)
Driver distraction has been recognised for a long time as a significant road safety issue. It has been consistently reported that drivers spend considerable time engaged in activities that are secondary to the driving task. The temporary diversion of attention from safety-critical driving tasks has often been associated with various adverse driving outcomes, from minor driving errors to serious motor vehicle crashes. This investigation explored the role of the driving context on a driver's decision to engage in secondary activities not critical to the driving task. The study makes use of the Naturalistic Engagement in Secondary Tasks (NEST) dataset, a complementary dataset derived from the SHRP2 naturalistic dataset, the most extensive naturalistic study to date. An exploratory analysis showed interesting behavioural trends from drivers with higher engagement rates in left curves compared to right curves, while driving uphill compared to driving downhill, in low-density traffic scenarios compared to high-density traffic scenarios, and during afternoon periods compared to morning periods. Significant differences were found in engagement among the different secondary tasks in relation to locality, speed, and roadway design. A clustering analysis showed no significant associations between driving scenarios of similar characteristics and the type of secondary activity executed. Overall, these findings confirm that the road traffic environment influences distracted driving behaviour among car drivers.